Nuevos registros de macrohongos (Basidiomycota) para Colombia procedentes de un bosque seco tropical (2015)
ABSTRACT: We recorded in a tropical dry forest in the northeast of Colombia (Cesar Dept.) 12 species of macrofungi previously unknown for the country; Amanita aureofloccosa, A. crebresulcata (Amanitaceae), Daedalea flavida (Fomitopsidaceae), Ganoderma resinaceum (Ganodermataceae), Marasmius cohortalis (Marasmiaceae), Phellinus merrilli, P. aff. umbrinellus (Hymenochaetaceae), Phlebopus beniensis (Boletinellaceae), Podoschypha petalodes (Meruliaceae), Psathyrella murrilli (Coprinaceae), Rigidoporus ulmarius (Meripilaceae) and Trametes socotrana (Polyporaceae). Each species is described, its taxonomic relationships are discussed, and some observations on its distribution and ecology are provided.